Cholesterol-recognizing amino acid consensus motifs in transmembrane proteins: Comparative analysis of in silico studies and structural data - Azzaz, Fodil (2022)
Fil: Azzaz, Fodil. Institut national de la santé et de la recherche médicale; Francia